The discourse of the “good death” in nineteenth-century fiction and a historical case study - Gadpaille, Michelle (ELOPE (Ljubljana), 2024)
What people said on their deathbeds preoccupied 19th-century Protestants. Fear of the void after death or of punishment in the afterlife made death terrifying. The process of dying, however, was ritualized to negate these terrors. Having a “good death” constituted reassurance for the dying, comfort for the family, and a lesson for the community. Such comfort was available even from fictional deathbed scenes, where sentiment and imagery softened the harsh reality. This interdisciplinary study explores the similarities between real and fictional deathbed narratives, using a sample of 19th-century novels, two historical deathbeds from Scotland, and a case study of an actual deathbed from the West Indies. The pattern of the good death – in both fiction and biography – includes specific elements such as witness, testimony, requests and advice, music, scripture, and confident hope of Heaven. Some deathbeds even became virtual stages or pulpits, with the dying person at the centre.
Keywords: angleška književnost; colonial Jamaica; English literature; kolonijalna Jamajka; Presbyterian missions; prezbiterianski misijoni; umiranje; Victorian deathbeds; Victorian novels; viktorijanski romani